Comparative Analysis of the Natural Gas Sector in Ukraine and the Czech Republic, Threats and Development Prospects - BOIKO, Oleksandr; KUNZ, Antonín; KLEMPA, Martin; BUJOK, Petr (GeoScience Engineering, 2021)
The natural gas sector plays a significant role in the energy sector. In Ukraine, natural gas accounts for about 30 % of the total consumption of energy resources, while in the Czech Republic only about 16 %. The article presents a comparative analysis of the natural gas sector in Ukraine and the Czech Republic in 2010–2019. The dynamics of changes in the production and consumption of natural gas in the discussed countries is presented. The structure of primary energy consumption, including natural gas, in 2018 and 2019 was analyzed. The analysis also covered the import of natural gas to Ukraine and the Czech Republic for own demand. Ukraine still has to import natural gas to meet its own demand, but in recent years, there have been drastic changes in the import of natural gas – and import dependency decreased by about 24 % in the analyzed period [1,2]. On the other hand, in the Czech Republic, the import of natural gas fluctuated within a limited range, and the import dependence increased by about 27 % compared to 2010 [1,3,4]. The article also deals with the problems of the gas pipeline system supplying natural gas from Russia to European countries. Keywords: Energy resources; Natural gas; Natural gas import.